P.038 Clinical experience with perampanel for refractory pediatric epilepsy in one Canadian center. (2nd June 2017) - Xu, H; Sachedina, S; Huh, L; Boelman, C; Connolly, M; Datta, A
Abstract : Background: Perampanel (PER) is a new anti-seizure medication that inhibits the α-amino-3-hydroxy-5-methyl-4-isoxazole-propionic acid (AMPA) class of glutamate receptors. It is available in Canada for children since 2014. It is important for physicians to be aware of the efficacy and tolerability of drugs in the post-marketing phase.Methods: We did a retrospective review of our experience with PER at BC Children's Hospital. Patients on PER were identified. Clinical data, including demographics, efficacy, tolerability, adverse effects (AE) and retention rates were obtained by review of clinical records.Results: Of 24 patients pediatric patients prescribed PER, 21 (87%) had focal and three had symptomatic generalized epilepsy. Ten (42%) had greater than 50% reduction in seizures. In fifteen patients, (63%) PER was discontinued due to AE or poor response. Twelve (50%) had behavioral AE and eight (33%) had non-behavioral AE. PER was effective, at lower doses than required for adults. One third experienced serious AE. One patient experienced oculogyric crisis, not previously reported with PER. AE were not associated with high doses and were reversible. Possible risk factors for behavioral AE include behavioral problems with other medications and pre-existing behavioral co-morbidities.Conclusions: It is important for clinicians to be aware of and counsel patients about serious AE, particularly behavioral, when prescribing PER.